Perovskite thin film and perovskite solar cell

By regulating the crystallization direction of perovskite through volatile ion additives to form vertically oriented grains, the problem of poor crystallization quality of the perovskite light absorption layer is solved, and high carrier transfer efficiency and improved battery stability are achieved.

CN120769689APending Publication Date: 2025-10-10嘉兴阿特斯阳光能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511118120.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

The crystallization quality of the perovskite light absorption layer in existing perovskite solar cells is poor, resulting in the presence of holes, small grain size and numerous grain boundaries, which affects the photovoltaic conversion efficiency and stability.

Method used

Volatile ion additives are used to regulate the crystallization direction of perovskite, and vertically oriented grains are formed through a two-step annealing process. The pore pathways are used to guide the vertical growth of the grains to form a dense lamellar structure, fill lattice defects and dislocations, and passivate defect states and unpaired bonds at grain boundaries.

Benefits of technology

It improves carrier mobility and lifetime, enhances the battery efficiency and stability of perovskite films, reduces non-radiative recombination, and improves photoelectric conversion efficiency and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120769689A_ABST
    Figure CN120769689A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite thin film and a perovskite solar cell, and belongs to the field of photovoltaic technology. The perovskite thin film comprises vertical orientation crystal grains, and the vertical orientation crystal grains are composed of a plurality of vertical sheet structures. According to the perovskite thin film provided by the invention, the vertical orientation crystal grains are composed of the plurality of vertical sheet structures, the carrier transmission paths among the plurality of vertical sheet structures are relatively short, and the preferred orientation crystal structure weakens the scattering effect on carriers, so that the mobility of the carriers is improved, and the performance of the perovskite thin film is improved. And because the grain boundary interface is less and the defect concentration is reduced, the service life of electrons in the perovskite thin film is longer, the diffusion distance is more obvious, and the opportunity of forming current by long-distance migration of the electrons is increased. Therefore, the structure of the perovskite thin film achieves the effects of low defect state and high carrier transmission efficiency, the improvement of the battery efficiency is facilitated, and the improvement of the battery stability is also facilitated through the compact and orderly arranged crystal grains and fewer defect sites.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is application number: 2025102797666, application date: 2025-03-11, name: A divisional application for a perovskite film, a preparation method thereof, and a perovskite solar cell. Technical Field

[0002] The present invention belongs to the field of photovoltaic technology, and in particular relates to a perovskite film and a perovskite solar cell. Background Art

[0003] Due to the advantages of low cost and simple process, the research and development of perovskite solar cells (PSCs) have received widespread attention, and the photoelectric conversion efficiency has rapidly increased to a level comparable to that of traditional crystalline silicon solar cells.

[0004] In the structure of PSCs, the perovskite light-absorbing layer is a key structure for generating photogenerated carriers. Its morphology and crystallization quality significantly affect the performance of perovskite solar cells. Given that different components in perovskite materials affect the crystallization process, when the film crystallization quality is poor, the presence of holes inside the perovskite light-absorbing layer, small grain size, and excessive grain boundaries will significantly affect the photovoltaic conversion efficiency and stability of the device.

[0005] Therefore, how to obtain a perovskite light absorption layer with fewer defect states and longer carrier lifetime is a key factor in determining the performance of perovskite solar cells. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a perovskite film and a perovskite solar cell. In the preparation method provided by the present invention, the introduction of volatile ion additives is used to slow down the crystallization rate of perovskite and regulate the crystallization direction of perovskite. During the first annealing process, the unbonded volatile anions are released in a very short time in the form of gas while the perovskite seed layer is formed, resulting in the existence of pore pathways inside the seed layer. During the second annealing process, the gas pathways guide the vertical orientation growth of the grains, and the resulting vertically oriented grains form a dense structure with vertical lamellae inside. This preparation method helps to fill defects and dislocations in the lattice, improve the integrity of the lattice structure, passivate defect states in the film and unpaired bonds at the grain boundaries, reduce non-radiative recombination, and improve the mobility and lifetime of carriers.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a perovskite thin film, the preparation method comprising the following steps:

[0009] The perovskite precursor solution and the volatile ion additive are mixed to obtain a modified perovskite precursor solution.

[0010] The modified perovskite precursor solution is coated on a substrate to form a wet film, and then a first annealing is performed to form a pore path perpendicular to the substrate inside the seed layer. Then a second annealing is performed to allow the crystals to grow along an orientation perpendicular to the substrate to form vertically oriented grains composed of a plurality of vertical lamellar structures, thereby obtaining the perovskite film; wherein the temperature of the first annealing is greater than the temperature of the second annealing, and the holding time of the first annealing is less than the holding time of the second annealing.

[0011] The preparation method provided by the present invention utilizes the introduction of volatile ion additives to slow the crystallization rate of perovskite and regulate its crystallization direction. During the first annealing step, unbonded volatile anions escape as gas in a very short time while forming a perovskite seed layer, creating pore pathways within the seed layer. During the second annealing step, the gas pathways guide the vertically oriented growth of the grains, ultimately resulting in a dense, vertically flaky structure within the vertically oriented grains. This preparation method helps fill defects and dislocations in the lattice, improve the integrity of the lattice structure, passivate defect states in the film and unpaired bonds at grain boundaries, reduce non-radiative recombination, and improve carrier mobility and lifetime.

[0012] The structure of the perovskite film obtained based on the preparation method provided by the present invention achieves the effects of low defect states and high carrier transfer efficiency, which is beneficial to improving battery efficiency. At the same time, the densely and orderly arranged grains and fewer defect sites are also beneficial to improving battery stability.

[0013] Preferably, the temperature of the first annealing step is greater than the volatilization temperature of the volatile anion in the volatile ion additive.

[0014] Preferably, the temperature of the first annealing step is 180-260°C, for example, it can be 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C or 260°C.

[0015] In the present invention, an appropriate annealing temperature facilitates the full volatilization of volatile anions, thereby forming tiny pore pathways, which lay the foundation for the oriented growth of crystals in the subsequent second annealing step. If the temperature of the first annealing step is too low, it is not conducive to the rapid formation of pore pathways, thus affecting the preferred orientation growth of grains; if the temperature of the first annealing step is too high, it will lead to irreversible decomposition of the perovskite film and performance collapse.

[0016] Preferably, the holding time of the first annealing step is a first preset time, and the first preset time is the time it takes for the wet film to change from a first color to a second color.

[0017] In the present invention, during the first annealing step, the temperature is high, causing the solvent in the modified perovskite precursor solution to evaporate rapidly, and the crystal structure begins to transform from disordered to ordered. This transformation changes the material's light absorption and scattering properties, resulting in a color change. When the color change is complete, it indicates that the initial solvent volatilization process has been completed and the initial crystal growth has ended. If the holding time of the first annealing step is too long, that is, the holding time of the first annealing step is longer than the time it takes for the wet film to transform from the first color to the second color, the continued high-temperature annealing will cause irreversible damage to the perovskite crystal components, affecting the battery performance.

[0018] Exemplarily, the first color is brown-black, and the second color is off-white; it is understandable that the first color and the second color are determined by the composition of the perovskite precursor solution, and are not limited to the specific colors listed in the present invention.

[0019] Preferably, the holding time of the first annealing step is 1-10 s, for example, it can be 1 s, 2 s, 3 s, 4 s, 5 s, 6 s, 7 s, 8 s, 9 s or 10 s.

[0020] In the present invention, under appropriate holding times, the perovskite precursor material has higher mobility, which can more effectively fill defects and dislocations in the lattice, improving the integrity of the lattice structure. If the holding time is too long, it will cause negative effects such as decomposition of perovskite film components, morphological degradation, and interface failure.

[0021] Preferably, the temperature of the first annealing step is 200-250° C., and the holding time is 2-4 seconds.

[0022] The present invention selects a specific temperature range and holding time, which, in synergistic cooperation, contribute to the full volatilization of volatile anions and the formation of tiny pore pathways, which not only ensure the integrity of the lattice structure but also lay the foundation for the subsequent preferential orientation growth of grains.

[0023] Preferably, the temperature of the second annealing step is 80-150°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.

[0024] In the present invention, annealing at a lower temperature can effectively reduce the thermal stress and defects that may be generated during high-temperature rapid annealing, especially the stress and strain at the interface between perovskite and other layers; it can also reduce overburning and material decomposition caused by high temperature, maintain the integrity of the material, and reduce the loss of electrical properties.

[0025] Preferably, the holding time of the second annealing step is 15-40 min, for example, 15 min, 20 min, 25 min, 30 min or 40 min.

[0026] In the present invention, the appropriate second-step annealing time enables the various components in the titanium ore material to gradually migrate and recombine to form uniform and large-sized grains; the appropriate second-step annealing time also helps to further passivate the defect states in the film and the unpaired bonds at the grain boundaries, reduce non-radiative recombination, and improve the mobility and lifetime of carriers. At the same time, it can also reduce overburning and material decomposition caused by high temperature, maintain the integrity of the material, and reduce the loss of electrical properties.

[0027] Preferably, the temperature of the second annealing step is 90-120° C., and the holding time is 15-30 minutes.

[0028] The present invention selects a specific temperature range and holding time, and the two work together to not only form uniform and large-sized grains, but also effectively improve the mobility and life of carriers, maintain the integrity of the material, and reduce the loss of electrical properties.

[0029] Preferably, in the volatile ionic additive, the volatilization temperature of the volatile anion is ≥100°C, for example, it can be 110°C, 130°C, 150°C, 170°C, 190°C, 200°C, 220°C, 240°C or 260°C.

[0030] Preferably, the volatile anion in the volatile ion additive includes any one of formate ion, acetate ion, propionate ion or oxalate ion, or a combination of at least two thereof.

[0031] Preferably, the cation in the volatile ion additive includes any one of formamidine ion, methylamine ion, cesium ion, lead ion or tin ion, or a combination of at least two thereof.

[0032] Preferably, the volatile ionic additive comprises lead acetate.

[0033] Preferably, the molar ratio of the perovskite precursor to the volatile ion additive in the perovskite precursor solution is 1:(0.02-0.1), for example, it can be 1:0.02, 1:0.04, 1:0.06, 1:0.08 or 1:0.1.

[0034] In the present invention, if the molar ratio of the perovskite precursor to the volatile ion additive is too small, that is, the amount of the volatile ion additive added is too much, the excess additive will precipitate, which is not conducive to the formation of high-quality perovskite film; if the molar ratio of the perovskite precursor to the volatile ion additive is too large, that is, the amount of the volatile ion additive added is too small, it is not conducive to the formation of effective grain preferential orientation and the enhancement of the crystallization quality of the film grains.

[0035] Preferably, the low-temperature slow annealing atmosphere is an air atmosphere.

[0036] Preferably, the relative humidity in the annealing atmosphere of the second annealing step is 20-50%, for example, 20%, 30%, 35%, 40%, 45% or 50%.

[0037] In the present invention, the second step annealing is carried out in an atmosphere with a certain humidity. The trace amount of water vapor in the atmosphere can serve as a morphology regulator in the crystallization process. By forming and decomposing an intermediate phase (such as PbI2·H2O), the crystallization activation energy is reduced, and larger grains and denser films are induced. Since the H2O in the atmosphere partially dissociates into -OH during annealing, it can react with uncoordinated Pb 2+ The combination forms Pb-OH bonds, thereby passivating the surface dangling bonds and improving the stability of the perovskite film.

[0038] Preferably, the preparation method comprises the following steps:

[0039] (1) adding a volatile ion additive to a perovskite precursor solution and mixing the mixture to obtain a modified perovskite precursor solution;

[0040] The molar ratio of the perovskite precursor to the volatile ion additive in the perovskite precursor solution is 1:(0.02-0.1); the volatile anions in the volatile ion additive include any one of formate ions, acetate ions, or oxalate ions, or a combination of at least two thereof; and the cations include any one of formamidine ions, methylamine ions, cesium ions, lead ions, or tin ions, or a combination of at least two thereof.

[0041] (2) The perovskite precursor solution is coated on a substrate, and then placed on a heating table, and a first annealing is performed at a temperature of 180-260°C and an inert atmosphere. The holding time of the first annealing is 1-10s, so that the volatile anions are volatilized, thereby forming a pore passage perpendicular to the substrate inside the seed layer, and then cooled to room temperature. Subsequently, a second annealing is performed at a temperature of 80-150°C and an air atmosphere with a relative humidity of 20-50%. The holding time of the second annealing is 15-40min, so that the grains grow along the orientation perpendicular to the substrate, forming vertically oriented grains with a crystal texture structure, and obtaining the perovskite film.

[0042] In a second aspect, the present invention provides a perovskite film, wherein the perovskite film includes vertically oriented grains, and the vertically oriented grains are composed of a plurality of vertical lamellar structures.

[0043] The vertical oriented grains in the perovskite film provided by the application are composed of a plurality of vertical sheet structures, and the carrier transport path between the plurality of vertical sheet structures is short, which significantly weakens the scattering effect of the crystal on the carriers, thereby greatly improving the mobility of the carriers, and because the grain boundary interface is less and the defect concentration is reduced, the lifetime of the electrons in the perovskite film is longer and the diffusion distance is more significant, thereby increasing the opportunity for long-distance migration of electrons to form current. Therefore, the structure of the perovskite film achieves the effect of low defect state and high carrier transport efficiency, which is beneficial to the improvement of the battery efficiency, and at the same time, the densely ordered grains and the fewer defect sites are also beneficial to the improvement of the stability of the battery.

[0044] It should be noted that "a plurality of" means at least 2, for example, 4, 10, 50, 100 or 500, etc.

[0045] It should be noted that "vertical oriented grains" represent that the grains and the plane of the perovskite film are in a substantially vertical relationship, that is, the plane of the grains and the plane of the perovskite film can be completely vertical, or not completely vertical but slightly inclined to the completely vertical direction.

[0046] Similarly, "a plurality of vertical sheet structures" represent that the plane of the sheet structure and the plane of the perovskite film are in a substantially vertical relationship, that is, the plane of the sheet structure and the plane of the perovskite film can be completely vertical, or not completely vertical but slightly inclined to the completely vertical direction.

[0047] Preferably, the grain size of the perovskite film is 1-3 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm, etc.

[0048] The perovskite film provided by the application has large-size vertical oriented grains with vertical sheet structures, which can provide a smoother transport path for carriers, reduce the interaction of carriers with grain boundary defects during transport, and enable the carriers to be more efficiently transported to the electrode, thereby improving the collection efficiency of the carriers and further improving the photoelectric conversion efficiency of the device. In addition, the large-size grains can make the crystal structure of the perovskite film more complete and ordered, which is beneficial to increasing the propagation path length of light in the film and improving the light absorption efficiency. In addition, under the action of external environmental factors (such as temperature, humidity, light, etc.), the perovskite film with large-size and dense grains is less likely to change structure and degrade, and can maintain good performance stability.

[0049] Preferably, the vertically oriented grains have an average longitudinal size of 500-1000 nm, for example, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm or 1000 nm, and preferably 700-800 nm.

[0050] In the present invention, the appropriate longitudinal average size can make the combination between grains tighter, improve the overall strength of the material, and effectively reduce the influence of grain boundaries on electron scattering, so that the carrier transmission in the material is less hindered.

[0051] Preferably, the carrier mobility of the perovskite film is 20-50 cm 2 / (V·s), for example, it can be 20cm 2 / (V·s), 30cm 2 / (V·s), 40cm 2 / (V·s) or 50cm 2 / (V·s), etc.

[0052] The perovskite film provided by the present invention has high carrier mobility and can effectively improve the photoelectric conversion efficiency of the battery.

[0053] Preferably, the perovskite film has a general chemical formula of ABX3, wherein A comprises any one or a combination of at least two of formamidinium ions, methylamine ions, or cesium ions, B comprises lead ions and / or tin ions, and X is a halogen ion. For example, FAPbI3 may be used.

[0054] In a third aspect, the present invention provides a perovskite solar cell, comprising a stacked substrate, a perovskite film, a first charge transfer layer, and an electrode, wherein the perovskite film is prepared by the preparation method described in the first aspect, or is the perovskite film described in the first aspect.

[0055] Preferably, the substrate includes a conductive base and a second charge transport layer stacked in a direction close to the perovskite film.

[0056] Preferably, the first charge transport layer and the second charge transport layer transport charges of opposite electrical properties. For example, the first charge transport layer is an electron transport layer and the second charge transport layer is a hole transport layer, or the first charge transport layer is a hole transport layer and the second charge transport layer is an electron transport layer.

[0057] Preferably, the second charge transport layer is an electron transport layer, and the first charge transport layer is a hole transport layer. For example, the electron transport layer may be, for example, a SnO2 layer, and the hole transport layer may be, for example, a 2,2',7,7'-tetrakis(N,N-bis(4-methoxyphenyl)amino)-9,9'-spirobifluorene (Spiro-OMeTAD) layer.

[0058] Preferably, the thickness of the electron transport layer is 5-15 nm, for example, 5 nm, 8 nm, 10 nm, 12 nm or 15 nm.

[0059] Preferably, the thickness of the hole transport layer is 15-25 nm, for example, 15 nm, 20 nm or 25 nm.

[0060] Preferably, the conductive substrate comprises transparent conductive glass, for example, ITO (indium tin oxide) conductive glass or FTO (fluorine-doped tin oxide) conductive glass.

[0061] Preferably, the thickness of the perovskite film is 500-1000 nm, for example, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm or 1000 nm.

[0062] Preferably, an interface modification layer is further provided between the perovskite film and the first charge transport layer, and the material of the interface modification layer includes any one of PEAI (phenylethylammonium iodide), PDAI (polydopamine), PMMA (polymethyl methacrylate) or NMAI (N-methylacrylimide) or a combination of at least two thereof.

[0063] In the present invention, the function of the interface modification layer is to passivate the upper surface defects of the perovskite film.

[0064] Preferably, the thickness of the interface modification layer is 1-10 nm, for example, 1 nm, 3 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.

[0065] Preferably, the electrode is made of metal, for example, Ag or Au.

[0066] The numerical range described in the present invention includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] (1) In the preparation method provided by the present invention, the introduction of volatile ion additives is used to slow down the crystallization rate of perovskite and regulate the crystallization direction of perovskite. During the first annealing process, the unbonded volatile anions overflow in the form of gas in a very short time while the perovskite seed layer is formed, resulting in the existence of pore channels inside the seed layer. During the second annealing process, the gas channels guide the vertical orientation growth of the grains, and the resulting vertically oriented grains form a dense structure with vertical lamellae. This preparation method helps to fill defects and dislocations in the lattice, improve the integrity of the lattice structure, passivate defect states in the film and unpaired bonds at the grain boundaries, reduce non-radiative recombination, and improve the mobility and lifetime of carriers.

[0069] (2) The vertically oriented grains in the perovskite film provided by the present invention are composed of a number of vertical sheet structures. The carrier transmission path between the vertical sheet structures is relatively short. This preferentially oriented crystal structure weakens its scattering effect on carriers, thereby improving the carrier mobility. In addition, due to the fewer grain boundaries, the defect concentration is reduced, resulting in a longer lifetime of electrons in the perovskite film and a more significant diffusion distance, thereby increasing the chance of electrons migrating over long distances to form current. Therefore, the structure of the perovskite film achieves the effect of low defect states and high carrier transmission efficiency, which is beneficial to the improvement of battery efficiency. At the same time, the dense and orderly arranged grains and fewer defect sites are also beneficial to the improvement of battery stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] Figure 1 This is a schematic structural diagram of the perovskite solar cell provided in Example 1 of the present invention.

[0071] Figure 2 This is a surface SEM image of the perovskite film provided in Example 1 of the present invention.

[0072] Figure 3 This is a cross-sectional SEM image of a partial structure of a perovskite solar cell provided in Example 1 of the present invention.

[0073] Figure 4 This is a surface SEM image of the perovskite film provided in Comparative Example 1 of the present invention.

[0074] Figure 5 This is a cross-sectional SEM image of a partial structure of a perovskite solar cell provided in Comparative Example 1 of the present invention.

[0075] Among them, 1-high-transmittance glass; 2-FTO layer; 3-electron transport layer; 4-perovskite film; 5-interface modification layer; 6-hole transport layer; 7-Au electrode. DETAILED DESCRIPTION

[0076] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0077] It should be noted that the room temperature below refers to 25°C.

[0078] Example 1

[0079] This embodiment provides a perovskite film, in which crystal grains have a growth orientation perpendicular to the substrate, so that the perovskite film forms a crystal texture structure with a vertical orientation.

[0080] The chemical formula of the perovskite film is FAPbI3, the average grain size of the perovskite film is 1500nm, and the carrier mobility of the perovskite film is 38cm 2 / (V·s).

[0081] This embodiment also provides a method for preparing the above-mentioned perovskite film, the preparation method comprising the following steps:

[0082] (1) Lead acetate is added to a FAPbI3 precursor solution having a concentration of 1.4 mol / L and mixed to obtain a modified perovskite precursor solution.

[0083] Among them, the molar ratio of FAPbI3 precursor and lead acetate is 1:0.06.

[0084] (2) Providing a substrate, the specific steps include:

[0085] A 2×2 cm area with a resistivity of 7Ω·sq -1 The FTO conductive glass was ultrasonically cleaned in 2% Hellmanex detergent, deionized water, acetone and ethanol for 30 minutes each, dried with clean dry air, and then irradiated in an ultraviolet ozone (UVO) instrument for 15 minutes;

[0086] The diluted SnO2 glue (the SnO2 glue with a volume fraction of 15% was diluted according to SnO2:H2O=1:3) was spin-coated on the FTO conductive glass at a speed of 3000 rpm for 30 seconds, and then annealed at 150°C for 30 minutes to form an electron transport layer.

[0087] Depositing a perovskite film, the specific steps include:

[0088] 28 μL of the perovskite precursor solution was dropped onto the surface of the electron transport layer of the substrate, and spin-coated at a speed of 4000 rpm for 30 seconds. 100 μL of chlorobenzene was added as an anti-solvent at the 7th second of spin coating. After spin coating, it was placed on a heating table and rapidly annealed at a temperature of 250°C and a nitrogen atmosphere for 5 seconds, so that the acetate ions volatilized, thereby forming a pore passage inside the seed layer. The film was then cooled to room temperature and subsequently transferred to air with a relative humidity of 40%. Slow annealing was performed at a temperature of 100°C for 20 minutes, so that the grains grew in an orientation perpendicular to the substrate to form a crystal texture structure with a vertical orientation, thereby obtaining the perovskite film.

[0089] This embodiment also provides a perovskite solar cell, the structural diagram of which is shown in FIG. Figure 1 As shown, the perovskite solar cell includes a stacked FTO conductive glass, an electron transport layer 3, the perovskite film 4 as described above, an interface modification layer 5, a hole transport layer 6 and an Au electrode 7.

[0090] The FTO conductive glass comprises a stacked high-transmittance glass 1 and an FTO layer 2. The high-transmittance glass 1 is 2 mm thick and has a light transmittance of 96%. The FTO layer 2 is 6 nm thick. The electron transport layer 4 is a SnO2 layer with a thickness of 10 nm. The interface modification layer 5 is a PEAI layer with a thickness of 5 nm. The hole transport layer 6 is a Spiro-OMeTAD layer with a thickness of 20 nm. The Au electrode 7 is 100 nm thick.

[0091] This embodiment also provides a method for preparing the above-mentioned perovskite solar cell, comprising the following steps:

[0092] (a) Using the above-described method for preparing a perovskite film, a SnO2 layer and a perovskite film were sequentially prepared on FTO conductive glass.

[0093] (b) 60 μL of PEAI solution (mass concentration of 10 mg / mL, solvent is isopropanol) was dropwise added onto the perovskite film and spin-coated at a speed of 4000 rpm for 30 s to form a PEAI layer.

[0094] (c) 20 μL of Spiro-OMeTAD solution was dropped onto the PEAI layer and spin-coated at 4000 rpm for 40 s to form a Spiro-OMeTAD layer.

[0095] (d) A layer of Au electrode is deposited on the outer surface of the Spiro-OMeTAD layer by vacuum evaporation.

[0096] Figure 2The surface SEM diagram of the perovskite thin film provided by embodiment 1 is shown, and it can be seen from the diagram that the crystal grains in the perovskite thin film provided by the application have a crystal texture structure (a plurality of substantially parallel strip-shaped structures), which indicates that the part of the crystal grains in the perovskite thin film close to the surface of the perovskite thin film is a sheet structure. Further, Figure 3 The cross-sectional SEM diagram of the partial structure of the perovskite solar cell provided by embodiment 1 is shown, and the perovskite thin film 4 in the diagram includes a plurality of vertical texture structures, which indicates that not only the part of the crystal grains in the perovskite thin film 4 close to the surface of the perovskite thin film 4 is a sheet structure, but also the crystal grains inside are vertical sheet structures; at the same time, it also indicates that the crystal grains of the perovskite thin film are also vertically oriented. Therefore, in combination with Figure 2 and Figure 3 It can be shown that the structure of the perovskite thin film provided by the application includes vertically oriented crystal grains, and the vertically oriented crystal grains are composed of a plurality of vertical sheet structures, which achieves the effect of low defect state and high carrier transport efficiency, is beneficial to the improvement of the battery efficiency, and at the same time, the densely and orderly arranged crystal grains and the fewer defect sites are also beneficial to the improvement of the stability of the battery.

[0097] Embodiment 2

[0098] The difference between this embodiment and embodiment 1 is that the molar ratio of the FAPbI3 precursor and lead acetate is 1:0.02.

[0099] The average size of the crystal grains of the perovskite thin film provided by this embodiment is 900 nm, and the carrier mobility is 25 cm 2 / (V·s).

[0100] The rest of the preparation method and parameters remain the same as those of embodiment 1.

[0101] Embodiment 3

[0102] The difference between this embodiment and embodiment 1 is that the molar ratio of the FAPbI3 precursor and lead acetate is 1:0.04.

[0103] The average size of the crystal grains of the perovskite thin film provided by this embodiment is 1200 nm, and the carrier mobility is 33 cm 2 / (V·s).

[0104] The rest of the preparation method and parameters remain the same as those of embodiment 1.

[0105] Embodiment 4

[0106] The difference between this embodiment and embodiment 1 is that the molar ratio of the FAPbI3 precursor and lead acetate is 1:0.1.

[0107] The average size of the crystal grains of the perovskite thin film provided by this embodiment is 1800 nm, and the carrier mobility is 30 cm2 / (V·s).

[0108] The rest of the preparation methods and parameters remained the same as in Example 1.

[0109] Example 5

[0110] The difference between this embodiment and embodiment 1 is that lead acetate is replaced by lead formate.

[0111] The average grain size of the perovskite film provided in this embodiment is 1400 nm, and the carrier mobility is 35 cm 2 / (V·s).

[0112] The rest of the preparation methods and parameters remained the same as in Example 1.

[0113] Example 6

[0114] The difference between this embodiment and embodiment 1 is that lead acetate is replaced by lead oxalate.

[0115] The average grain size of the perovskite film provided in this embodiment is 1450 nm, and the carrier mobility is 33 cm 2 / (V·s).

[0116] The rest of the preparation methods and parameters remained the same as in Example 1.

[0117] Example 7

[0118] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the temperature of the rapid annealing is 180° C., the temperature of the slow annealing is 80° C., and the time of the slow annealing is 25 minutes.

[0119] The average grain size of the perovskite film provided in this embodiment is 1300 nm, and the carrier mobility is 30 cm 2 / (V·s).

[0120] The rest of the preparation methods and parameters remained the same as in Example 1.

[0121] Example 8

[0122] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the rapid annealing temperature is 220° C., the rapid annealing time is 3 s, and the slow annealing temperature is 150° C., the slow annealing time is 15 min.

[0123] The average grain size of the perovskite film provided in this embodiment is 1400 nm, and the carrier mobility is 33 cm 2 / (V·s).

[0124] The rest of the preparation methods and parameters remained the same as in Example 1.

[0125] Example 9

[0126] The difference between this embodiment and embodiment 1 is that the molar ratio of the FAPbI3 precursor to lead acetate is 1:0.01.

[0127] The rest of the preparation methods and parameters remained the same as in Example 1.

[0128] Example 10

[0129] The difference between this embodiment and embodiment 1 is that the molar ratio of the FAPbI3 precursor to lead acetate is 1:0.15.

[0130] The rest of the preparation methods and parameters remained the same as in Example 1.

[0131] Example 11

[0132] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the temperature of the rapid annealing is 150°C.

[0133] The rest of the preparation methods and parameters remained the same as in Example 1.

[0134] Example 12

[0135] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the temperature of the rapid annealing is 280°C.

[0136] The rest of the preparation methods and parameters remained the same as in Example 1.

[0137] Example 13

[0138] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the rapid annealing time is 8 seconds.

[0139] The rest of the preparation methods and parameters remained the same as in Example 1.

[0140] Example 14

[0141] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the temperature of the slow annealing is 70°C.

[0142] The rest of the preparation methods and parameters remained the same as in Example 1.

[0143] Example 15

[0144] The difference between this embodiment and embodiment 1 is that in the step of depositing the perovskite film, the temperature of the slow annealing is 160°C.

[0145] The rest of the preparation methods and parameters remained the same as in Example 1.

[0146] Comparative Example 1

[0147] The difference between this comparative example and Example 1 is that step (1) is not performed, that is, lead acetate is not introduced into the APbI3 precursor solution.

[0148] The rest of the preparation methods and parameters remained the same as in Example 1.

[0149] Figure 4 and Figure 5 The surface SEM image and cross-sectional SEM image of the perovskite film provided in this comparative example are shown respectively. It can be seen from the figures that the grains of the perovskite film provided in this comparative example have no crystal texture structure and do not show a lamellar structure.

[0150] Performance Testing

[0151] The photoelectric performance and stability of the perovskite solar cells provided in the above embodiments and comparative examples were tested.

[0152] Photoelectric performance test conditions: AM1.5, 1000W / m 2 , 25±2℃.

[0153] Stability test conditions: The battery was subjected to a 1000-hour stability test in an air environment (relative humidity of 20-40%), and the ratio of the battery efficiency after 1000 hours to the original efficiency was recorded.

[0154] The test results are shown in Table 1.

[0155] Table 1

[0156]

[0157] analyze:

[0158] As can be seen from the above table, the present invention utilizes the introduction of volatile ion additives to slow down the crystallization rate of perovskite and regulate the crystallization direction of perovskite. During the high-temperature rapid annealing process, the unbonded volatile anions overflow in the form of gas in a very short time while forming the perovskite seed layer, resulting in the existence of pore pathways inside the seed layer. During the low-temperature slow annealing process, the gas pathways guide the vertical orientation growth of the grains, ultimately forming a dense structure with vertical textures. The structure of the perovskite film prepared based on this preparation method achieves the effects of low defect states and high carrier transfer efficiency, which is beneficial to the improvement of battery efficiency. At the same time, the dense and orderly arranged grains and fewer defect sites are also beneficial to the improvement of battery stability.

[0159] It can be seen from Examples 1 and 9-10 that if the molar ratio of the FAPbI3 precursor to lead acetate is too small, that is, the amount of lead acetate added is too much, it is not conducive to improving the battery efficiency and stability; if the molar ratio of the FAPbI3 precursor to lead acetate is too large, that is, the amount of lead acetate added is too little, it will not have the effect of significantly improving the battery efficiency and stability.

[0160] It can be seen from Examples 1 and 11-12 that if the rapid annealing temperature is too low, the preferential orientation growth of the perovskite film grains will be affected, which is not conducive to the transport of carriers; if the rapid annealing temperature is too high, it will cause the decomposition of some components, which is not conducive to the stability of the crystal structure.

[0161] It can be seen from Example 1 and Example 13 that if the rapid annealing time is too long, it will be detrimental to the crystallization of the perovskite film grains, and if the high temperature time is too long, it will cause the decomposition of the components, thereby affecting the electrical properties.

[0162] It can be seen from Examples 1 and 14-15 that if the slow annealing temperature is too low, the perovskite grains will not be fully crystallized, the defect state will increase, and the overall performance will deteriorate; if the slow annealing temperature is too high, the overheated grains will be thermally decomposed, causing irreversible effects on stability.

[0163] It can be seen from Example 1 and Comparative Example 1 that the introduction of volatile ion additives can improve the crystallization quality of the perovskite film, and the interface between the perovskite film and the charge transport layer is free of holes, which increases the carrier extraction capacity and extraction rate, thereby significantly improving the efficiency and stability of the resulting battery.

[0164] While the present invention is illustrated by the above-described embodiments, the present invention is not limited to the above-described process steps, and implementation of the present invention is not necessarily dependent on the above-described process steps. Those skilled in the art will appreciate that any improvements to the present invention, equivalent substitutions for the raw materials used, additions of auxiliary components, and selection of specific methods, etc., fall within the scope of protection and disclosure of the present invention.

Claims

1. A perovskite film, characterized in that: The perovskite film includes vertically oriented grains, which are composed of a plurality of vertical sheet structures.

2. The perovskite thin film according to claim 1, characterized in that The average grain size of the perovskite film is 1-3 μm; and / or, the vertically oriented grains have an average longitudinal size of 500-1000 nm; And / or, the carrier mobility of the perovskite film is 20-50 cm 2 / (V·s).

3. The perovskite film according to claim 2, characterized in that The vertical average size of the vertically oriented grains is 700-800 nm.

4. The perovskite thin film according to claim 1, characterized in that There are Pb-OH bonds on the surface of the perovskite film, and the surface dangling bonds are passivated.

5. The perovskite thin film according to claim 1, characterized in that The vertically oriented grains are in a completely perpendicular relationship to the plane where the perovskite film is located, or are slightly inclined to the completely perpendicular direction; And / or, the plane where the sheet structure is located and the plane where the perovskite film is located may be completely perpendicular to each other, or slightly inclined to the completely perpendicular direction.

6. The perovskite thin film according to claim 1, characterized in that The grains in the perovskite film have a crystal texture structure; The portion of the grains in the perovskite film close to the surface of the perovskite film is a plurality of sheet-like structures; The interior of the grains in the perovskite film exhibits a vertical sheet-like structure.

7. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a stacked substrate, a perovskite film, a first charge transport layer and an electrode, and the perovskite film is the perovskite film according to any one of claims 1 to 6.

8. The perovskite solar cell according to claim 7, characterized in that The substrate includes a conductive base and a second charge transport layer stacked in a direction close to the perovskite film; The first charge transport layer and the second charge transport layer transport charges of opposite electrical properties.

9. The perovskite solar cell according to claim 8, characterized in that The second charge transport layer is an electron transport layer, and the first charge transport layer is a hole transport layer; And / or, the thickness of the electron transport layer is 5-15 nm; and / or, the hole transport layer has a thickness of 15-25 nm; And / or, the thickness of the perovskite film is 500-1000 nm.

10. The perovskite solar cell according to claim 7, characterized in that An interface modification layer is further provided between the perovskite film and the first charge transport layer, wherein the material of the interface modification layer comprises any one of PEAI, PDAI, PMMA or NMAI or a combination of at least two thereof; The thickness of the interface modification layer is 1-10 nm.